New trends in the changes of administrative boundaries in Poland - Kociuba, Dagmara (European Spatial Research and Policy, 2021)
The objective of the study is to determine the leading trends in changing administrative boundaries in Poland. Based on 194 Regulations of the Council of Ministers concerning the changes of boundaries and granting city status, which covered a total of 1,383.8 sq. km, multidimensional analyses for the years 2010–2020 were conducted, and their results were referred to territorial reforms in Europe and Poland. The analyses provided the basis for selecting the leading trends, including: (1) the ‘new wave’ of the restitution of city status (from 2018 in the new fast-track mode), resulting in quantitative changes within 3rd-tier units, (2) a significant increase in the area of cities and city counties primarily caused by annexations in suburban zones and establishing new cities, and (3) the politicisation of the process of changing boundaries, especially in the years preceding local government elections. The trend of unit fragmentation observed in the 1990s has disappeared. The initiators of the changes of administrative boundaries are still predominantly local elites and rarely the inhabitants of communes.